W poszukiwaniu rezultatów… Polityka Unii Europejskiej wobec Białorusi - Kubin, Tomasz (Studia Politicae Universitatis Silesiensis, 2018)
Abstract: In the search of results… European Union Politics to Belarus The way A. Łukaszenka, a Belarusian president has a power, a political situation in this country and its foreign policy have shaped the relationship between Belarus and European Union as well as its members differently than the EU relationships with other European countries for more or less the 1950’s. As a result, the EU policy towards Belarus differs a lot from other East-European countries. The aim of the article is to present an outline of the EU Policy towards Belarus within the scope of two decades (from getting independence by Belarus in 1991 to the beginning of 2011), and the most important factors that influence the EU-Belarusian relationship. The first part of the article also shows the factors that make Belarus an important country for the EU, while in conclusion there is an attempt to analyse and evaluate the effects of the EU policy towards Belarus. Key words: EU — Belarusian relationships, Belarus in politics, Common Foreign and EU Safety Policy, EU neighbourhood policy